Cell lineage-specific expression of modulo, a dose-dependent modifier of variegation in Drosophila. - Garzino, V.; Pereira, A.; Laurenti, P.; Graba, Y.; Levis, R.W.; Le Parco, Y.; Pradel, J. (The EMBO Journal, 1992)
Variegation in Drosophila is a manifest illustration of the important role played by chromatin structure in gene expression. We have isolated mutants of modulo (mod) and shown that this gene is a dominant suppressor of variegation. Null mutants are recessive lethal with a melanotic tumour phenotype. The mod protein directly binds DNA, which indicates that it may serve to anchor multimeric complexes promoting chromatin compaction and silencing. Using a specific monoclonal antibody we examined by immunocytochemistry the accumulation pattern of mod protein during embryogenesis. The protein is first detected before the blastoderm cellularization in all somatic nuclei, precisely when pericentromeric heterochromatin becomes visible. After the first cell division, mod protein is expressed in lineages of specific embryonic primordia. Based on its dominant phenotype, expression pattern and DNA-binding activity of its product, we propose that mod regulates chromatin structure and activity in specific cell lineages.